Deregulasi Terhadap Paradoks Vaksin Covid-19 Sebagai Barang Publik Dan Vaksin Berbayar Dalam Peraturan Menteri Kesehatan Nomor 19 Tahun 2021 - Ahsan, Fikri (UI Scholars Hub, 2022)
The Coronavirus Virus Disease 2019 (COVID-19) vaccine coronavirus (COVID-19) on pandemics is public goods that make public use of all societies in general, but in the regulation of the minister of health number 19 of 2021 regarding the second amendment to the regulation of the minister of health number 10 of 2021 regarding the implementation of vaccinations in the wake of the corona virus virus 2019 (COVID-19) vaccine, Explains the cooperative vaccination that funding is imposed on individuals/individuals (paid). This goes against public goods and tends to become commercial private goods, so in this pandemic of covid-19 should not be sold commercially for any reason, even if it is governed by legislation.